Crosstalk between the Akt/mTORC1 and NF-κB signaling pathways promotes hypoxia-induced pulmonary hypertension by increasing DPP4 expression in PASMCs - Li Ying; Yang Li; Dong Liang; Yang Zhi-wei; Zhang Jing; Zhang Sheng-li; Niu Meng-jie; Xia Jing-wen; Gong Yi; Zhu Ning; Zhang Xiu-juan; Zhang Yuan-yuan; et al. (Acta Pharmacologica Sinica; Vol 40, No 10 (October 2019): Acta Pharmacologica Sinica, 2019)
Abnormal wound healing by pulmonary artery smooth muscle cells (PASMCs) promotes vascular remodeling in hypoxia-induced pulmonary hypertension (HPH). Increasing evidence shows that both the mammalian target of rapamycin complex 1 (mTORC1) and nuclear factor-kappa B (NF-κB) are involved in the development of HPH. In this study, we explored the crosstalk between mTORC1 and NF-κB in PASMCs cultured under hypoxic condition and in a rat model of hypoxia-induced pulmonary hypertension (HPH). We showed that hypoxia promoted wound healing of PASMCs, which was dose-dependently blocked by the mTORC1 inhibitor rapamycin (5−20 nM). In PASMCs, hypoxia activated mTORC1, which in turn promoted the phosphorylation of NF-κB. Molecular docking revealed that mTOR interacted with IκB kinases (IKKs) and that was validated by immunoprecipitation. In vitro kinase assays and mass spectrometry demonstrated that mTOR phosphorylated IKKα and IKKβ separately. Inhibition of mTORC1 decreased the level of phosphorylated IKKα/β, thus reducing the phosphorylation and transcriptional activity of NF-κB. Bioinformatics study revealed that dipeptidyl peptidase-4 (DPP4) was a target gene of NF-κB; DPP4 inhibitor, sitagliptin (10−500 μM) effectively inhibited the abnormal wound healing of PASMCs under hypoxic condition. In the rat model of HPH, we showed that NF-κB activation (at 3 weeks) was preceded by mTOR signaling activation (after 1 or 2 weeks) in lungs, and administration of sitagliptin (1−5 mg/kg every day, ig) produced preventive effects against the development of HPH. In conclusion, hypoxia activates the crosstalk between mTORC1 and NF-κB, and increased DPP4 expression in PASMCs that leads to vascular remodeling. Sitagliptin, a DPP4 inhibitor, exerts preventive effect against HPH.